On the wedge between the PPI and CPI inflation indicators - Shang-jin Wei; Yinxi Xie (Bank of Canada, 2022)
While two strands of the literature suggest that PPI inflation, in addition to or instead of CPI inflation, should be a targeting variable in a monetary policy rule, the distinction between the two is only important when they do not co-move strongly. Our first contribution is to document that their correlation has indeed fallen substantially since the start of this century. Our second contribution is to propose a model to understand this divergence based on expanding global supply chains. Our theory produces additional predictions that are also confirmed in the data. As such changes are structural rather than temporary, the standard monetary policy rule that does not target the PPI inflation may have become increasingly problematic.
Keywords: E31; E52; E58; F11; F12; F41; F62; 330; Inflation and prices; Inflation targets; International topics; Monetary policy